2006
DOI: 10.1127/0003-9136/2006/0166-0117
|View full text |Cite
|
Sign up to set email alerts
|

An environmental assessment of an impacted, urbanized watershed: the Mona Lake Watershed, Michigan

Abstract: The ecological health and integrity of watersheds throughout the world are being threatened by a variety of stressors. Often, restoration practices focus on single problems whereas comprehensive, multidisciplinary approaches are needed to address both the symptoms and underlying causes of impairment. A comprehensive assessment of a small, urbanized watershed in west Michigan, USA was conducted to evaluate the major stressors in the system. This assessment approach for the Mona Lake watershed included analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…During summer stratification and anoxic conditions, internal phosphorus loading accounts for 68-82% of the overall phosphorus load in Mona Lake (Steinman et al, 2009), and may be responsible for promoting and maintaining algal blooms (Cymbola et al, 2008). These blooms may be prolonged into the fall season when lake turnover brings up bottom waters high in phosphorus and ammonia (Freedman et al, 1979;Steinman et al, 2006), which is the preferred source of nitrogen for algae. Recent studies have indicated that the phytoplankton in Mona Lake appear to be limited by either nitrogen or co-limited by phosphorus and nitrogen Biddanda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During summer stratification and anoxic conditions, internal phosphorus loading accounts for 68-82% of the overall phosphorus load in Mona Lake (Steinman et al, 2009), and may be responsible for promoting and maintaining algal blooms (Cymbola et al, 2008). These blooms may be prolonged into the fall season when lake turnover brings up bottom waters high in phosphorus and ammonia (Freedman et al, 1979;Steinman et al, 2006), which is the preferred source of nitrogen for algae. Recent studies have indicated that the phytoplankton in Mona Lake appear to be limited by either nitrogen or co-limited by phosphorus and nitrogen Biddanda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The harmful algal blooms are one of the major impairments affecting Mona Lake, a drowned river-mouth lake with water quality degradation and a history of impairment (Evans, 1992;Steinman et al, 2006). Mona Lake's two main tributaries experienced pollution from various industries (e.g., petroleum refinery, metal finishing plant, superfund site) and are placed on the state of Michigan's 303(d) list for impaired fish and macroinvertebrate communities.…”
Section: Introductionmentioning
confidence: 99%
“…Four tributaries account for [95% of the annual discharge to Mona Lake under base flow conditions: Black Creek (77.2%), Little Black Creek (9.3%), Cress Creek (5.3%), and Ellis Drain (4.7%; Steinman et al 2006). Black Creek originates as a series of agricultural ditches in the upper reaches of the watershed before flowing through forested areas, and then residential reaches on its way to Mona Lake (Fig.…”
Section: Study Sitementioning
confidence: 99%
“…Changing land use patterns, including increases in urbanization, drainage efficiency, and impervious surface area, have resulted in faster nutrient delivery to water bodies, with less opportunity for removal by abiotic or biotic processes Steinman et al 2006). Attempts to limit or reduce external loading to water bodies have resulted in the development of low impact development initiatives in many municipalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation